2022
DOI: 10.1093/molbev/msac061
|View full text |Cite
|
Sign up to set email alerts
|

Selection Analysis Identifies Clusters of Unusual Mutational Changes in Omicron Lineage BA.1 That Likely Impact Spike Function

Abstract: Among the 30 non-synonymous nucleotide substitutions in the Omicron S-gene are 13 that have only rarely been seen in other SARS-CoV-2 sequences. These mutations cluster within three functionally important regions of the S-gene at sites that will likely impact (i) interactions between subunits of the Spike trimer and the predisposition of subunits to shift from down to up configurations, (ii) interactions of Spike with ACE2 receptors, and (iii) the priming of Spike for membrane fusion. We show here that, based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
106
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(107 citation statements)
references
References 68 publications
1
106
0
Order By: Relevance
“…In late November 2021, a distinct SARS-CoV-2 variant emerged (B.1.529) that had an unusual cluster of mutations, especially in the spike gene (5, 6). There was an unprecedented and rapidly disseminated series of studies on this variant, which was subsequently named “Omicron” by the World Health Organization.…”
Section: Introductionmentioning
confidence: 99%
“…In late November 2021, a distinct SARS-CoV-2 variant emerged (B.1.529) that had an unusual cluster of mutations, especially in the spike gene (5, 6). There was an unprecedented and rapidly disseminated series of studies on this variant, which was subsequently named “Omicron” by the World Health Organization.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the mutations shared by BA.1 and BA.2, if taken individually, would have been predicted to significantly decrease viral fitness. Nevertheless, they are thought to cooperatively interact by positive epistasis, mitigating the negative fitness costs associated with their presence and possibly altering some biological properties of the spike protein (Martin et al, 2022b). Insertion XLI (i.e.…”
Section: Resultsmentioning
confidence: 99%
“… 36 Compared with SARS-CoV-2 WT, Omicron has 53 more mutations, of which 34 mutations occurred in the S protein region, 13 mutations cluster within three functionally important regions of the S-gene seem cooperatively interact to mitigate their individual fitness costs and adaptively alter the function of SARS-CoV-2 S protein. 37 A recent study confirmed that Omicron S protein binds more strongly to hACE2 than other variants, and it mediates enhanced entry into cells expressing several different animal ACE2s, including various domestic avian species, horseshoe bats and mice, suggesting it has an increased propensity for reverse zoonosis and is more likely to establish an animal reservoir of SARS-CoV-2 than previous variants. 38 Another study also found that the N501Y and Q498 R in Omicron could enable the variant to bind rat ACE2 with increased affinity to almost 20-fold, which would be expected to drive increased human-to-human and cross-species transmission.…”
Section: Discussionmentioning
confidence: 96%